MACARIE THE HIEROMONK AND THE TRANSLATION OF HYMNS INTO ROMANIAN. CASE STUDY: HEIRMOS OF "PENTECOST" - MOCANU, Daniel (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2016)
The goal of our paper is to explain the special importance which the Pentecost Heirmos has within Macarie, the Hieromonk’s creation (1750-1836), one of the most outstanding figures of the ecclesiastical Byzantine music in the Romanian area. We intend to undertake a comparative musical-literary analysis of Heirmos IX at the Feast of Pentecost, composed by Petros Lampadarios and translated by Macarie the Hieromonk. We will inventorize the solutions that Macarie found for solving the prosodic and metric differences between Greek and Romanian. He noticed the impact those solutions had on the melodic path of the Heirmos (the place of the cadential formulas). In addition to the version based on Petros Lampadarios’ composition, Macarie the Hieromonk, also wrote an original Pentecost Heirmos. It was based on Byzantine bases, which, due to its melodic and composition particularities, has been considered a masterpiece of the Romanian Byzantine church music.